Sharia-Based Financial Performance Optimization for MSMEs in Banten Province, Indonesia - Itang Itang; Sam’un Jaja Raharja; Rusdin Tahir; Wawan Wahyuddin (Khazanah Sosial, 2023)
Economic growth will be influenced by stable Small and Medium Enterprises (SMEs) and optimal financial performance based on the use of sharia fintech. This study aims to examine the financial sustainability and performance of MSMEs from the perspective of Islamic economics; examine the impact of sharia fintech use on the financial sustainability and performance of SMEs; and strengthen human resource capacity, business diversification, business productivity, and product marketing to enhance the financial sustainability and business sustainability of SMEs. The survey was conducted with a quantitative approach. Data was obtained through questionnaires distributed to 303 respondents in 4 cities and 4 districts in Banten Province. The findings indicated that company diversification and human resource capacity had an impact on the financial performance of MSMEs. The viability of SME firms is positively impacted by sharia fintech, human resource capability, company diversification, business productivity, and financial performance. Our study recommends SME business management based on the use of sharia fintech in supporting SME business sustainability in Banten Province, Indonesia. Our research contribution, apart from being empirical evidence of how to optimize MSME financial performance, also provides understanding for MSME managers in inventorying alternatives to improve financial performance by studying human resource capacity, business diversification, sharia Fintech, and business productivity, which in turn has an impact on economic growth.